Uso do lodo de curtume na produção de plantas de açaizeiro em fase inicial de desenvolvimento - Da Silva, George Rodrigues; Amaral, Idemê Gomes; Galvão, Jessivaldo Rodrigues; Pinheiro, Daniel Pereira [UNESP]; Da Silva, Mario Lopes; Melo, Nilvan Carvalho [UNESP] (Revista Brasileira de Ciencias Agrarias, 2015)
Currently tannery sludge, waste from leather processing industry, has been widely used in agriculture. This residue has nutrient content that can be used by plants, but has potentially toxic elements that can cause damage to the environment and human health. The objective of this study was to evaluate the effect of different ratios of tannery sludge used as substrate in the growth of plants açaizeiro and chemical changes occurring in the substrate 180 days after planting the plants. We used a completely randomized design with six replications. The treatments consisted of the following substrates: control (soil without tannery sludge), soil + 50 % of tannery sludge, soil + 70 % of tannery sludge, soil + 75 % of tannery sludge, soil + 80 % of sludge tannery and 100 % of tannery sludge. All plants were evaluated açaizeiro height, stem diameter, root length. And root dry weight, shoot and total. N, K, Ca, Mg, and Na contents: In the substrate the pH, organic matter and the contents of the chemical elements essences plants were evaluated. We also assessed the levels of potentially toxic element: Cd, Cr, Cu, Fe, Mn, Pb and Zn. The use of tannery sludge as substrate, decreased plant growth of açai, increased the contents essences of plants and the elements Na, and promote increased levels of potentially toxic elements. However, the increase in the levels of potentially toxic elements was in the range allowed by current environmental legislation in the country, in other words, at levels that do not cause environmental problems.
Use of sludge tanning in production plants açaizeiro in initial phase of development
Keywords: Euterpe oleracea; Industrial waste; Phytoremediation. nutrients; Potentially toxic elements